STRATEGI MANAJEMEN KEPEMIMPINAN TRANSFORMASIONAL DALAM PENGELOLAAN KEARSIPAN - Abdul Rahman Saleh; Arini Wahyuniati; Farel Nurul Arifin; Naovan Dwi Nurmala; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational leadership and organizational culture play a strategic role in improving the effectiveness of archival management in schools. Effective archival management is essential to support administrative order, accountability, and decision-making processes in educational institutions. This study aims to analyze the role of educational leadership and organizational culture in enhancing the effectiveness of archival management in schools. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results show that educational leadership contributes significantly through policy-making, supervision, and fostering a culture of discipline. Meanwhile, organizational culture strengthens archival management through shared values, work habits, and institutional commitment. The synergy between leadership and organizational culture creates an effective, efficient, and sustainable archival management system. Keywords: Educational Leadership, Organizational Culture, Archival Management, Effectiveness, School Administration